2008
DOI: 10.1016/j.eurpsy.2008.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive insight and verbal memory in first episode of psychosis

Abstract: Beck and collaborators have proposed a distinction between clinical insight and cognitive insight and have developed a tool for the assessment of the latter, namely the Beck Cognitive Insight Scale (BCIS). The present study explored in 51 patients with a first episode of psychosis the neurocognitive correlates of cognitive insight as assessed with the BCIS. Global measures for seven domains of cognition including verbal learning and memory, visual learning and memory, working memory, speed of processing, reaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
47
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 45 publications
8
47
3
Order By: Relevance
“…36 Similarly, another group of researchers has shown that the neurocognitive domains of verbal learning and memory, as well as attention, were significantly correlated with Composite Index and Self-Certainty; the Composite Index, additionally, was associated with social cognition; and neither the SUMD nor the PANSS correlated with neurocognitive or social cognitive measures. 21 A second study by this group largely corroborated these findings, with the exception that Self-Reflectiveness (rather than Self-Certainty) correlated with verbal memory. 29 This last study was also the first to report brain imaging results.…”
Section: Functional Outcomesupporting
confidence: 69%
See 4 more Smart Citations
“…36 Similarly, another group of researchers has shown that the neurocognitive domains of verbal learning and memory, as well as attention, were significantly correlated with Composite Index and Self-Certainty; the Composite Index, additionally, was associated with social cognition; and neither the SUMD nor the PANSS correlated with neurocognitive or social cognitive measures. 21 A second study by this group largely corroborated these findings, with the exception that Self-Reflectiveness (rather than Self-Certainty) correlated with verbal memory. 29 This last study was also the first to report brain imaging results.…”
Section: Functional Outcomesupporting
confidence: 69%
“…Convergent validity has been determined by correlating the BCIS with 5 different measures of clinical insight. Two groups have replicated the finding of Beck et al that the Composite Index correlated with the SUMD, finding moderate-to-large correlations with the Awareness of a Mental Illness item 21 and the total score.…”
Section: 12supporting
confidence: 68%
See 3 more Smart Citations